PENGEMBANGAN MODUL AJAR DEEP LEARNING SISTEM KELISTRIKAN BERBASIS PENDEKATAN PEMBELAJARAN MENDALAM UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMK YPP PURWOREJO - Noufal Hisyam Burhanudin; Suyitno; Arif Susanto (STKIP Subang, 2026)
This study aims to determine the development process, validity, practicality, and effectiveness of a deep learning-based teaching module on motorcycle electrical systems to improve student learning outcomes at SMK YPP Purworejo. The research employed the Research and Development (R&D) method using Sugiyono’s development model, which includes the stages of identifying potentials and problems, data collection, product design, design validation, design revision, product trial, product revision, usage trial, further revision, and mass production. The research subjects were Class XI TSM students at SMK YPP Purworejo. Data collection techniques included observation, interviews, questionnaires, and learning outcome tests. Results showed that: (1) the module was successfully developed through all R&D stages; (2) media validation yielded an average of 78% (sufficiently valid) and material validation 80.62% (valid); (3) the module was considered practical by both teachers and students; and (4) the module proved effective in improving learning outcomes, with the experimental class mean rising from 62.83 (pretest) to 83.67 (posttest), a gain of 20.84 points, compared to 62.80 to 72.17 in the control class. The independent samples t-test confirmed a significant difference (t = 7.459; sig. = 0.000 < 0.05). These findings confirm that the deep learning teaching module supports more active, adaptive, and contextual learning aligned with vocational education needs in the digital era.